Interpretasi Sosial terhadap Kekerasan Seksual dalam Perspektif Sekolah Berbasis Agama - Wendika Oktariani; Tri Wuryaningsih; Soetji Lestari (Departement of Mathematics Education, 2023)
This research aims to analyze and identify the school culture that develops in religious-based schools and to analyze the social interpretations of students in these schools regarding sexual violence. The research utilizes a systematic literature review approach, involving an analysis of literature on sexual violence that occurs in formal educational institutions. Sexual violence that occurs in religious-based school environments is caused by cultural factors that influence the occurrence of sexual violence within the context of learning. One significant cultural factor is the values embraced in the school culture, including the concept of student obedience to teachers. This concept provides space for teachers to engage in sexual violence, as it is perceived that students should submit and obey the authority of teachers without questioning or objection. This research will identify and analyze the social interpretations of students in religious-based schools regarding sexual violence. This will contribute to a better understanding of students' perspectives and experiences in the context of sexual violence in religious-based school environments. Through this understanding, more effective efforts can be developed to prevent and address sexual violence in schools, including changes in school culture and the adoption of inclusive and safe learning approaches for all students. The results of this research are expected to provide valuable insights for relevant parties, including schools, educators, and policymakers, to address the issue of sexual violence in religious-based school environments. By identifying cultural factors that contribute to sexual violence and understanding students' social interpretations, appropriate preventive measures and interventions can be designed and implemented. The ultimate goal is to create a safe, inclusive, and free-from-sexual-violence educational environment in religious-based schools.